Individual features of radiation-induced genomic instability in patients with glioblastoma - Zemskova, O.V.; Glavatsky, O.Ya.; Kurinnyi, D.A.; Demchenko, O.M.; Rushkovsky, S.R. (Reports of the National Academy of Sciences of Ukraine, 2020)
Using the method of Comet assay under neutral conditions, the features of individual radiation-induced genome instability in patients with glioblastoma was studied. It was found that, in the culture of peripheral blood lymphocytes of two patients with pathomorphologically verified glioblastoma (patients No. 1 and No. 3), the frequency of comets with a high level of DNA damage significantly exceeded the values in the cultures of blood lymphocytes of the comparison group. After irradiation in a dose of 1.0 Gy, the frequency of cells with a high DNA damage rate was increased in lymphocyte cultures of patients No. 2 and No. 3 and decreased in patient No. 1. Frequency analysis of the distribution of individual “comets” depending on their levels of DNA damage revealed the presence of a significant pool of cells in the lymphocyte cultures of patients No. 2 and No. 3 which stopped di vision at the S stage of the cell cycle. After the irradiation, the frequency of such cells in patient No. 3 decreased significantly. It was noted that apoptotic activity in cultures of lymphocytes of neuro-oncological patients was significantly higher than in cultures of conditionally healthy volunteers.